2024
DOI: 10.1038/s41390-024-03161-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow dynamics during cardiac surgery in infants

Martin Leth-Olsen,
Gaute Døhlen,
Hans Torp
et al.

Abstract: Background In this pilot study, we investigated continuous cerebral blood flow velocity measurements to explore cerebrovascular hemodynamics in infants with congenital heart disease undergoing cardiac surgery. Methods A non-invasive transfontanellar cerebral Doppler monitor (NeoDoppler) was used to monitor 15 infants (aged eight days to nine months) during cardiac surgery with cardiopulmonary bypass. Numerical and visual analyses were conducted to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…NIRS has been studied for its potential in monitoring cerebral oxygenation during different transcatheter procedures and in predicting complications, but more evidence is needed to show clinical benefits [ 21 , 22 , 23 ]. A previous study demonstrated that NIRS has a delayed response compared to CBFV in acute changes in cerebral perfusion during cardiac surgery with cardiopulmonary bypass in infants [ 24 ]. Invasive and non-invasive blood pressure monitoring are routinely used as a surrogate for cardiac output and cerebral perfusion during interventions.…”
Section: Discussionmentioning
confidence: 99%
“…NIRS has been studied for its potential in monitoring cerebral oxygenation during different transcatheter procedures and in predicting complications, but more evidence is needed to show clinical benefits [ 21 , 22 , 23 ]. A previous study demonstrated that NIRS has a delayed response compared to CBFV in acute changes in cerebral perfusion during cardiac surgery with cardiopulmonary bypass in infants [ 24 ]. Invasive and non-invasive blood pressure monitoring are routinely used as a surrogate for cardiac output and cerebral perfusion during interventions.…”
Section: Discussionmentioning
confidence: 99%